Functional water-based acrylic latex with rust conversion effect as well as preparation method and application of functional water-based acrylic latex
By combining the rust converter with acrylic latex through chemical bonding, a composite aqueous latex with strong stability is solved, and the problems of poor adhesion and insufficient corrosion resistance in actual applications of traditional aqueous acrylic latex are achieved, and rust conversion performance and corrosion resistance are achieved. Improved performance simplifies the preparation process and reduces the risk of corrosion.
Patent Information
- Application Number
- CN202411340053.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
AI Technical Summary
In actual application, traditional water-based acrylic latex has poor adhesion and insufficient corrosion resistance due to substrate pollution and uneven coating composition. It is difficult to achieve a uniform and stable state of rust converter and latex system physical mixing, which affects the thickness of the coating. and anti-corrosion effect.
By combining the rust converter and acrylic latex through chemical bonds, a composite aqueous latex with strong stability and uniform dispersion is formed. The rust converts active ingredients and acrylic latex polymer segments are used to connect the rust conversion active ingredients and the acrylic latex polymer segments, and the chelating agent is fixed to the polymer segments to form a chelating agent with Compound aqueous latex with rust conversion function avoids the risk of coating corrosion caused by improper proportion during construction.
It achieves strong stability, uniform dispersion and good corrosion resistance, simplifies the preparation process, reduces potential corrosion risks, and improves the adhesion and corrosion resistance of the coating.
Smart Images

Figure CN119161523A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a functional water-based acrylic latex, in particular to a functional water-based acrylic latex with rust conversion function, and also to a preparation method and application of the functional water-based acrylic latex. Background Art
[0002] Water-based metal anti-rust paint uses water as a dispersion medium, is environmentally friendly and safe, non-toxic, odorless and pollution-free. Compared with traditional oil-based anti-rust paint, water-based paint is non-flammable and non-explosive, safer, and helps protect the environment and fire safety. In addition, water-based metal anti-rust paint also has the advantages of stable performance and fast drying speed. It has gradually replaced traditional anti-rust paint and has been widely used in many fields such as automobiles, ships, petrochemicals, bridges, etc.
[0003] As an important base resin of water-based metal anti-rust coatings, water-based acrylic latex is widely used in water-based anti-rust coatings. Its preparation method is simple and the paint film dries quickly. However, due to problems in actual application scenarios, the actual application of water-based coatings has problems. For example, due to the presence of oil, rust particles, dust and other dirt on the substrate, or too much hydrophilic material in the coating, water can easily penetrate into the paint film, generating air pressure, thereby causing bubbling of the paint film. The anti-rust emulsion is not rust-proof or the surface tension of the coating is greater than the surface tension of the substrate, resulting in poor adhesion between the primer and the substrate, affecting water resistance, etc.
[0004] It is generally believed that adding rust converters to traditional water-based acrylic latex systems can effectively improve the above problems, such as simplifying the construction process, improving the hardness and adhesion of the coating, and optimizing the corrosion resistance of the coating. However, the traditional method is to physically mix the rust converter with the water-based acrylic latex system. However, physical mixing makes it difficult for the composite latex system to achieve a uniform and stable state, which in turn leads to high construction requirements, the thickness and uniformity of the rust layer cannot be guaranteed, and the ratio of the conversion liquid and the film-forming liquid is difficult to control. If the rust conversion is incomplete or the conversion liquid is used improperly, it may leave potential corrosion risks under the coating, affecting the long-term anti-corrosion effect of the coating. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a functional water-based acrylic latex with strong stability, uniform dispersion and rust conversion effect, and also provide a preparation method and application of the above composite water-based latex.
[0006] Technical solution: The functional water-based acrylic latex with rust conversion effect of the present invention comprises the following components in percentage by weight:
[0007] 2-9 wt% polymerizable gallic acid composite salt;
[0008] Acrylate monomer mixture 42-48 wt%;
[0009] Anionic emulsifier 0.5-2wt%;
[0010] Nonionic emulsifier 0.1-1wt%;
[0011] Water-soluble initiator 0.1-0.5wt%;
[0012] The balance is water.
[0013] The polymerizable gallic acid composite salt is obtained by acid-base neutralization reaction of gallic acid and an acrylate monomer with an amino functional group; specifically, the acrylate with an amino functional group is placed in a reaction kettle and heated to 60-90°C, and then gallic acid is added and stirred, the mass ratio of the acrylate with an amino functional group to gallic acid is 2-6:1, the stirring speed is controlled at 200-1000 rpm, the reaction is fully reacted, and the reaction time is controlled at 30-60 min.
[0014] Wherein, the acrylic acid ester monomer with amino functional group is N-hydroxymethyl acrylamide, or dimethylaminoethyl acrylate, or dimethylaminoethyl methacrylate.
[0015] Wherein, the acrylic ester monomer mixture comprises the following components in percentage by weight:
[0016] Methyl methacrylate 5-15wt%;
[0017] Styrene 45~60wt%
[0018] Hydroxyethyl acrylate 1-5wt%;
[0019] Isooctyl acrylate 18-35wt%;
[0020] Methacrylic acid 1-5wt%.
[0021] Wherein, the anionic emulsifier is one of a sulfate anionic emulsifier, a carboxylate emulsifier or a phosphate anionic emulsifier.
[0022] Wherein, the nonionic emulsifier is one of polyoxyethylene ether nonionic emulsifier, polyol fatty acid ester nonionic emulsifier or Tween 80.
[0023] Wherein, the functional water-based acrylic latex, the anionic emulsifier is a sulfate anionic emulsifier, specifically sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octyl styrene sulfate or sodium cocamide sulfate.
[0024] The functional water-based acrylic latex is a non-ionic emulsifier, which is a polyoxyethylene ether non-ionic emulsifier, specifically C8-C10 fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether.
[0025] Wherein, the water-soluble initiator is potassium persulfate or ammonium persulfate.
[0026] The method for preparing the functional water-based acrylic latex having a rust conversion effect comprises the following steps:
[0027] (1) adding a portion of anionic emulsifier, nonionic emulsifier and water-soluble initiator into water to form a mixed solution, then adding the acrylic ester monomer mixture and dispersing at high speed to obtain a pre-emulsified product;
[0028] (2) pouring the remaining anionic emulsifier, nonionic emulsifier and water-soluble initiator and polymerizable gallic acid composite salt into water and mixing and dispersing them uniformly, and then adding a portion of the pre-emulsified material obtained in step (1) to obtain a primer reaction product;
[0029] (3) heating the primer obtained in step (2) and stirring the reaction, and adding the remaining pre-emulsified material dropwise; after the addition is completed, the reaction is kept warm and cooled to obtain a functional water-based acrylic latex having a rust conversion effect.
[0030] Among them, in step (1) and step (2), the ratio of the amount of anionic emulsifier taken before and after is 40-50:50-60, the ratio of the amount of nonionic emulsifier taken before and after is 40-50:50-60, the ratio of the amount of water-soluble initiator taken before and after is 60-80:20-40, and the ratio of the amount of water taken before and after is 55-64:36-45; the pre-emulsion added in step (2) is 8-10wt% of the pre-emulsion prepared in step (1).
[0031] Wherein, in step (3), the heating and stirring reaction is carried out under the following conditions: heating to 75-80°C, stirring and reacting at a speed of 200-500 rpm for 0.1-1 hour, heating to 82-85°C, and gradually adding the remaining pre-emulsified material dropwise, with the addition time controlled at 3-5 hours.
[0032] Wherein, in step (3), the insulation is carried out under the conditions of a rotation speed of 500 to 1000 rpm and insulation at 85 to 88° C. for 2 to 5 hours.
[0033] The functional water-based acrylic latex having the rust conversion effect can also be used in the field of metal corrosion protection.
[0034] Among them, the metal anti-corrosion is specifically a metal protective coating, whose components include functional water-based acrylic latex with rust conversion effect, water-based dispersant, water-based defoaming agent, water-based leveling agent, water-based wetting agent, titanium dioxide, zinc phosphate, barium sulfate, water-based polyurethane thickener, distilled water, and alcohol ester twelve.
[0035] Principle of the invention: The present invention combines the rust conversion agent with the acrylic latex through chemical bonds, utilizes the chemical bond to stably disperse the two in the aqueous phase system, connects the rust conversion active ingredients with the acrylic latex polymer chain segments to obtain a composite water-based latex with strong stability, uniform dispersion, and rust conversion function. The chelating agent is fixed to the polymer chain segment, so that the gallic acid in the coating system forms a chelate with the metal ions generated during the corrosion process, which is beneficial to the rust conversion performance of the coating while having good corrosion resistance. In addition, the functional water-based acrylic latex of the present invention does not need to mix the conversion liquid with the polymer latex on site during the painting process, which avoids the coating corrosion caused by the improper ratio of the conversion liquid and the film-forming liquid in the traditional construction process, and also eliminates the potential corrosion risk.
[0036] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The functional water-based acrylic latex with rust conversion effect of the present invention is highly stable, evenly dispersed, and has good rust conversion performance and corrosion resistance; (2) The preparation process is simple, does not require anhydrous and oxygen-free operation, and does not require high-pressure reactor operation, which is conducive to industrial production and has great application prospects in the field of metal corrosion protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The morphology of the functional waterborne acrylic latex of the present invention dispersed in water observed by transmission electron microscopy;
[0038] Figure 2 The surface morphology of the functional water-based latex cured coating of the present invention observed by scanning electron microscopy;
[0039] Figure 3 The rusty iron plate is shown before (A) and after (B) coating with the latex prepared in Example 1. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below in conjunction with the embodiments. The test materials used can be purchased through conventional channels.
[0041] Example 1
[0042] The functional water-based acrylic latex with rust conversion effect of the present invention comprises the following components in percentage by weight:
[0043] Polymerizable gallic acid composite salt 5.5wt%;
[0044] Acrylate monomer mixture 42wt%;
[0045] Anionic emulsifier 1.5wt%;
[0046] Nonionic emulsifier 0.5wt%;
[0047] Water-soluble initiator 0.5wt%;
[0048] Deionized water 50wt%.
[0049] Among them, the preparation of polymerizable gallic acid composite salt, the raw materials are N-hydroxymethyl acrylamide and gallic acid in a mass ratio of 2:1, N-hydroxymethyl acrylamide is placed in a reactor and heated to 60°C, and then gallic acid is added and stirred. The stirring speed is controlled at 1000 rpm and the reaction is fully reacted for 60 minutes.
[0050] The acrylic acid ester monomer mixture includes the following components in weight percentage:
[0051]
[0052] Wherein, the functional water-based acrylic latex is sodium dodecyl sulfate, the functional water-based acrylic latex is C8-C10 fatty alcohol polyoxyethylene ether, and the water-soluble initiator is potassium persulfate.
[0053] The preparation method of the functional water-based acrylic latex comprises the following steps:
[0054] (1) adding a portion of anionic emulsifier, nonionic emulsifier, and water-soluble initiator into water to form a mixed solution, and then adding the acrylic ester monomer mixture, and dispersing at high speed to obtain a pre-emulsified product;
[0055] (2) pouring the polymerizable gallic acid composite salt, the remaining anionic emulsifier, the nonionic emulsifier, and the water-soluble initiator into water and mixing and dispersing them uniformly, adding 8 wt % of the pre-emulsified material obtained in step (1) to obtain a primer reaction product; the anionic emulsifier is used in a ratio of 40:60, the nonionic emulsifier is used in a ratio of 40:60, the water-soluble initiator is used in a ratio of 80:20, and the water is used in a ratio of 55:45;
[0056] (3) After the temperature is raised to 75° C. and the reaction is stirred at a speed of 200 rpm for 1 hour, the temperature is raised to 82° C. and the remaining pre-emulsified material is gradually added dropwise, and the adding time is controlled within 5 hours; after the pre-emulsified material is added dropwise, the temperature is kept at 85° C. and the rotation speed is 500 rpm for 5 hours, and then cooled to obtain a functional water-based acrylic latex with a rust conversion effect.
[0057] Take the functional water-based acrylic latex with rust conversion effect obtained in Example 1, such as Figure 1 As shown in the morphology observed by TEM (transmission electron microscope), it can be seen that the gallic acid salt with active double bonds is fixedly encapsulated in the polymer latex particles. Therefore, through the emulsion polymerization method of the present invention, the rust conversion agent gallic acid salt and the acrylic latex are chemically bonded and stably dispersed in the aqueous phase system.
[0058] Example 2
[0059] The functional water-based acrylic latex with rust conversion effect of the present invention comprises the following components in percentage by weight:
[0060] Polymerizable gallic acid complex salt 2wt%
[0061] Acrylate monomer mixture 48wt%
[0062] Anionic emulsifier 2wt%
[0063] Nonionic emulsifier 1wt%
[0064] Water-soluble initiator 0.1wt%;
[0065] Deionized water 46.9wt%.
[0066] Among them, the preparation of polymerizable gallic acid composite salt, the raw materials are dimethylaminoethyl acrylate and gallic acid in a mass ratio of 3:1. Dimethylaminoethyl acrylate is placed in a reactor and heated to 70°C, and then gallic acid is added and stirred. The stirring speed is controlled at 800 rpm and the reaction is fully reacted for 50 minutes.
[0067] The acrylic acid ester monomer mixture includes the following components in weight percentage:
[0068]
[0069] Wherein, the functional water-based acrylic latex is sodium cetyl sulfate, the functional water-based acrylic latex is C8-C10 fatty alcohol polyoxyethylene ether, and the water-soluble initiator is ammonium persulfate.
[0070] The preparation method of the functional water-based acrylic latex comprises the following steps:
[0071] (1) adding a portion of anionic emulsifier, nonionic emulsifier, and water-soluble initiator into water to form a mixed solution, and then adding the acrylic ester monomer mixture, and dispersing at high speed to obtain a pre-emulsified product;
[0072] (2) pouring the polymerizable gallic acid composite salt, the remaining anionic emulsifier, the nonionic emulsifier, and the water-soluble initiator into water and mixing and dispersing them uniformly, adding 8.8 wt % of the pre-emulsified material obtained in step (1) to obtain a primer reaction product; the anionic emulsifier is used in a ratio of 42:58, the nonionic emulsifier is used in a ratio of 42:58, the water-soluble initiator is used in a ratio of 75:25, and the water is used in a ratio of 58:42;
[0073] (3) After the temperature is raised to 76° C. and the reaction is stirred at a speed of 300 rpm for 0.8 hours, the temperature is raised to 83° C. and the remaining pre-emulsified material is gradually added dropwise, and the adding time is controlled to be 4.5 hours; after the pre-emulsified material is added dropwise, the temperature is kept at 86° C. and the rotation speed is 600 rpm for 4 hours, and then cooled to obtain a functional water-based acrylic latex with a rust conversion effect.
[0074] Example 3
[0075] The functional water-based acrylic latex with rust conversion effect of the present invention comprises the following components in percentage by weight:
[0076] Polymerizable gallic acid complex salt 8.8wt%
[0077] Acrylate monomer mixture 47.4wt%
[0078] Anionic emulsifier 0.5wt%
[0079] Nonionic emulsifier 0.9wt%
[0080] Water-soluble initiator 0.4wt%;
[0081] Deionized water 42wt%.
[0082] Among them, the preparation of polymerizable gallic acid composite salt, the raw materials are N-hydroxymethyl acrylamide and gallic acid in a mass ratio of 5:1. N-hydroxymethyl acrylamide is placed in a reactor and heated to 80°C, and then gallic acid is added and stirred. The stirring speed is controlled at 400 rpm and the reaction is fully reacted for 40 minutes.
[0083] The acrylic acid ester monomer mixture includes the following components in weight percentage:
[0084]
[0085] Wherein, the functional water-based acrylic latex is sodium cocamide sulfate, the functional water-based acrylic latex is alkylphenol polyoxyethylene ether, and the water-soluble initiator is ammonium persulfate.
[0086] The preparation method of the functional water-based acrylic latex comprises the following steps:
[0087] (1) adding a portion of anionic emulsifier, nonionic emulsifier, and water-soluble initiator into water to form a mixed solution, and then adding the acrylic ester monomer mixture, and dispersing at high speed to obtain a pre-emulsified product;
[0088] (2) pouring the polymerizable gallic acid composite salt, the remaining anionic emulsifier, the nonionic emulsifier, and the water-soluble initiator into water and mixing and dispersing them uniformly, adding 9.5 wt % of the pre-emulsified material obtained in step (1) to obtain a primer reaction product; the anionic emulsifier is used in an amount ratio of 48:52, the nonionic emulsifier is used in an amount ratio of 45:55, the water-soluble initiator is used in an amount ratio of 65:35, and the water is used in an amount ratio of 60:40;
[0089] (3) raising the temperature to 78° C., stirring and reacting at a speed of 400 rpm for 0.3 hour, raising the temperature to 84° C., and gradually dropping the remaining pre-emulsified material, wherein the dropping time is controlled within 3.5 hours; after the pre-emulsified material is dropped, keeping the temperature at 87° C. and a speed of 900 rpm for 3 hours, and cooling to obtain a functional water-based acrylic latex having a rust conversion effect.
[0090] Example 4
[0091] The functional water-based acrylic latex with rust conversion effect of the present invention comprises the following components in percentage by weight:
[0092] Polymerizable gallic acid complex salt 9wt%
[0093]
[0094] Among them, the preparation of polymerizable gallic acid composite salt, the raw materials are N-hydroxymethyl acrylamide and gallic acid in a mass ratio of 6:1. N-hydroxymethyl acrylamide is placed in a reactor and heated to 90°C, and then gallic acid is added and stirred. The stirring speed is controlled at 200 rpm and the reaction is fully reacted for 30 minutes.
[0095] The acrylic acid ester monomer mixture includes the following components in weight percentage:
[0096]
[0097] Wherein, the functional water-based acrylic latex is sodium octylstyrene sulfate, the functional water-based acrylic latex is alkylphenol polyoxyethylene ether, and the water-soluble initiator is potassium persulfate.
[0098] The preparation method of the functional water-based acrylic latex comprises the following steps:
[0099] (1) adding a portion of anionic emulsifier, nonionic emulsifier, and water-soluble initiator into water to form a mixed solution, and then adding the acrylic ester monomer mixture, and dispersing at high speed to obtain a pre-emulsified product;
[0100] (2) pouring the polymerizable gallic acid composite salt, the remaining anionic emulsifier, the nonionic emulsifier, and the water-soluble initiator into water and mixing and dispersing them uniformly, adding 10 wt% of the pre-emulsified material obtained in step (1) to obtain a primer reaction product; the anionic emulsifier is used in a ratio of 50:50, the nonionic emulsifier is used in a ratio of 50:50, the water-soluble initiator is used in a ratio of 60:40, and the water is used in a ratio of 64:36;
[0101] (3) raising the temperature to 80° C., stirring and reacting at a speed of 500 rpm for 0.1 hour, raising the temperature to 85° C., and gradually dropping the remaining pre-emulsified material, wherein the dropping time is controlled within 3 hours; after the pre-emulsified material is dropped, keeping the temperature at 88° C. and a speed of 1000 rpm for 2 hours, and cooling to obtain a functional water-based acrylic latex having a rust conversion effect.
[0102] Comparative Example 1
[0103] A composite latex, compared with Example 1, Comparative Example 1 is doped with unmodified polymerized gallic acid, comprising the following components in percentage by weight:
[0104]
[0105] Wherein, the acrylic ester monomer mixture includes the following components in weight percentage:
[0106]
[0107]
[0108] Wherein, the functional water-based acrylic latex is sodium dodecyl sulfate, the functional water-based acrylic latex is C8-C10 fatty alcohol polyoxyethylene ether, and the water-soluble initiator is potassium persulfate.
[0109] Comparative Example 2
[0110] An acrylic latex, compared with Example 1, Comparative Example 2 is not doped with modified polymerized gallic acid, and includes the following components in percentage by weight:
[0111]
[0112] Wherein, the acrylic ester monomer mixture includes the following components in weight percentage:
[0113]
[0114] Wherein, the functional water-based acrylic latex is sodium dodecyl sulfate, the functional water-based acrylic latex is C8-C10 fatty alcohol polyoxyethylene ether, and the water-soluble initiator is potassium persulfate.
[0115] Based on the functional waterborne acrylic latex with rust conversion effect prepared in Examples 1 to 4 of the present invention and the materials prepared in Comparative Examples 1 to 2, their application in metal protective coatings was verified:
[0116] The functional water-based acrylic latex with rust conversion effect prepared in Examples 1 to 4 and the materials prepared in Comparative Examples 1 to 2 were respectively used to prepare water-based acrylic metal anticorrosive coatings according to Table 1. The specific composition includes: functional water-based acrylic latex with rust conversion effect, water-based dispersant, water-based defoamer, water-based leveling agent, water-based wetting agent, titanium dioxide, zinc phosphate, barium sulfate, water-based polyurethane thickener, distilled water, and alcohol ester twelve.
[0117] Table 1. Water-based anticorrosive coatings based on the functional water-based acrylic latex of the present invention
[0118]
[0119]
[0120] The aqueous dispersant is: Dispersogen 2774 (Clariant); the aqueous defoamer is: Foamex3062 (Evonik, Germany); water-based leveling agent: BYK333 (BYK, Germany); water-based wetting agent: TegoDispers760W (Evonik, Germany); the particle size of titanium dioxide is 600 mesh, the particle size of zinc phosphate is 800 mesh, and the particle size of barium sulfate is 800 mesh.
[0121] Figure 3 For comparison, a rusty iron plate was coated with the water-based anticorrosive coating prepared in Example 1. The blackening phenomenon of the coating on the plate surface after drying indicates that the rust and the resin in the coating chelate to form a black paint film, which is beneficial to improve the mechanical and anticorrosive properties of the coating.
[0122] like Figure 1 The functional water-based acrylic latex with rust conversion effect prepared in Example 1 can be evenly dispersed in the water phase system, and its stability will not be affected by the copolymerization of the polymerizable gallic acid complex salt. Then, it is applied to the surface of the metal substrate by brushing, spraying or rolling. After being placed for 7 days, the surface morphology of the cured coating is observed by FESEM (field emission scanning electron microscope); Figure 2As shown, after coating and curing, the coating is smooth and uniform, indicating that the gallic acid salt is evenly dispersed in the polymer resin without aggregation, which is conducive to the uniform and stable mechanical and anti-corrosion properties of the coating.
[0123] The performance indicators of the above cured coating were further tested, as shown in Table 2:
[0124] Table 2 Performance indicators of water-based anticorrosive coatings based on functional water-based acrylic latex of the present invention
[0125]
[0126]
[0127] As can be seen from Table 2, the water-based anticorrosion coating based on the functional water-based acrylic latex with rust conversion effect that can be applied to metal protection of the present invention has mechanical properties that are not affected by the copolymerization of polymerizable gallic acid composite salts, relative to Comparative Examples 1 to 2. In anticorrosion applications, the coating has significantly improved salt spray resistance, freeze-thaw resistance, moisture and heat resistance, and other properties, and has broad application prospects in the field of metal protection.
Claims
1. A functional water-based acrylic latex with rust conversion effect, characterized in that: The functional water-based acrylic latex comprises the following components in percentage by weight: The balance is water.
2. The functional water-based acrylic latex according to claim 1, characterized in that: The polymerizable gallic acid composite salt is obtained by acid-base neutralization reaction of gallic acid and acrylate monomer with amino functional group; specifically, acrylate with amino functional group is placed in a reaction kettle and heated to 60-90°C, then gallic acid is added and stirred, the mass ratio of acrylate with amino functional group to gallic acid is 2-6:1, the stirring speed is controlled at 200-1000 rpm, the reaction is fully reacted, and the reaction time is controlled at 30-60min.
3. The functional water-based acrylic latex according to claim 1, characterized in that: The acrylic acid ester monomer mixture comprises the following components in percentage by weight:
4. The functional water-based acrylic latex according to claim 1, characterized in that: The anionic emulsifier is a sulfate anionic emulsifier, specifically sodium lauryl sulfate, sodium hexadecyl sulfate, sodium octylstyrene sulfate or sodium cocamide sulfate.
5. The functional water-based acrylic latex according to claim 1, characterized in that: The nonionic emulsifier is a polyoxyethylene ether nonionic emulsifier, specifically C8-C10 fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether.
6. The functional water-based acrylic latex according to claim 1, characterized in that: The water-soluble initiator is potassium persulfate or ammonium persulfate.
7. A method for preparing the functional water-based acrylic latex having rust conversion effect as claimed in claim 1, characterized in that: The following steps are involved: (1) adding a portion of anionic emulsifier, nonionic emulsifier and water-soluble initiator into water to form a mixed solution, then adding the acrylic ester monomer mixture and dispersing at high speed to obtain a pre-emulsified product; (2) pouring the remaining anionic emulsifier, nonionic emulsifier and water-soluble initiator and polymerizable gallic acid composite salt into water and mixing and dispersing them uniformly, and then adding a portion of the pre-emulsified material obtained in step (1) to obtain a primer reaction product; (3) heating the primer obtained in step (2) and stirring the reaction, and adding the remaining pre-emulsified material dropwise; after the addition is completed, the reaction is kept warm and cooled to obtain a functional water-based acrylic latex having a rust conversion effect.
8. The method according to claim 7, characterized in that: In step (1) and step (2), the ratio of the amount of anionic emulsifier taken before and after is 40-50:50-60, the ratio of the amount of nonionic emulsifier taken before and after is 40-50:50-60, the ratio of the amount of water-soluble initiator taken before and after is 60-80:20-40, and the ratio of the amount of water taken before and after is 55-64:36-45; the pre-emulsion added in step (2) is 8-10wt% of the pre-emulsion prepared in step (1).
9. The method according to claim 7, characterized in that: In step (3), the heating and stirring reaction is carried out under the following conditions: heating to 75-80°C, stirring and reacting at a speed of 200-500 rpm for 0.1-1 hour, heating to 82-85°C, and gradually dropping the remaining pre-emulsified material, with the dropping time controlled at 3-5 hours.
10. The method according to claim 7, characterized in that: In step (3), the heat preservation is carried out under the conditions of a rotation speed of 500 to 1000 rpm and a heat preservation of 85 to 88° C. for 2 to 5 hours.
11. Use of the functional water-based acrylic latex with rust conversion effect as claimed in claim 1 in the field of metal corrosion protection.
